Sediment Accumulation and Carbon Burial in Four Hadal Trench Systems. Issue 10 (3rd October 2022) - Oguri, Kazumasa; Masqué, Pere; Zabel, Matthias; Stewart, Heather A.; MacKinnon, Gillian; Rowden, Ashley A.; Berg, Peter; Wenzhöfer, Frank; Glud, Ronnie N.
Abstract: Hadal trenches are considered to act as depocenters for organic material, although pathways for the material transport and deposition rates are poorly constrained. Here we assess focusing, deposition and accumulation of material and organic carbon in four hadal trench systems underlying different surface ocean productivities; the eutrophic Atacama and Kuril‐Kamchatka trenches, the mesotrophic Kermadec trench and the oligotrophic Mariana Trench. The study is based on the distributions of naturally occurring 210 Pbex, 137 Cs and total organic carbon from recovered sediment cores and by applying previously quantified benthic mineralization rates. Periods of steady deposition and discreet mass‐wasting deposits were identified from the profiles and the latter were associated with historic recorded seismic events in the respective regions. During periods without mass wasting, the estimated focusing factors along trench axes were elevated, suggesting more or less continuous downslope focusing of material toward the interior of the trenches. The estimated organic carbon deposition rates during these periods exhibited extensive site‐specific variability, but were generally similar to values encountered at much shallower settings such as continental slopes and margins. Organic carbon deposition rates during periods of steady deposition were not mirrored by surface ocean productivity, but appeared confounded by local bathymetry. The inclusion of deposition mediated by mass‐wasting events enhanced the sediment and organic carbon accumulations for the past ∼150 years by up to a factor of ∼4. Thus, due to intensified downslope material focusing and infrequent mass‐wasting events, hadal trenches are important sites for deposition and sequestration of organic carbon in the deep sea. Plain Language Summary: Hadal trenches (>6, 000 m water depth) occupy ∼1% of the world's ocean floor yet are largely underexplored, but recent studies have shown that these environments are depocenters for organic material and microbial activity is intensified when compared to shallower abyssal plains. However, transport and accumulation of sediment material to these hadal trenches is poorly understood. This study investigates sedimentation and accumulation dynamics of organic carbon in trenches using results of radionuclide analysis (in sediment from the Atacama, Kuril‐Kamchatka, Kermadec, and Mariana trenches). The analysis shows that trench sediments consist of discreet layers representing both periods of continuous deposition and sudden mass‐wasting events often triggered by historic earthquakes. Down slope focusing of material, intensified the deposition along the trench axes. However, the deposition rates exhibited extensive site‐specific variations that were partly related to mass‐wasting events which greatly enhanced not only mass accumulation but also organic carbon accumulation at the trench axes. Our results illustrate that mass‐wasting events play an important role on supplying organic carbon to hadal communities and suggest that hadal trenches might be quantitatively important for sediment and organic carbon sequestration in the deep sea. Key Points: Hadal trench systems act as important hot spots for accumulation and retention of organic material in the deep sea The sediment and organic carbon accumulation in trench systems is partly mediated by ongoing material focusing Infrequent mass‐wasting events triggered by earthquakes play a significant role on mass accumulation and organic carbon deposition